2020
DOI: 10.1016/j.artd.2020.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Opioid Prescriptions Lowers Consumption Without Detriment to Patient-Reported Pain Interference Scores After Total Hip and Knee Arthroplasties

Abstract: Background: Opioid addiction is endemic in the United States. We developed a standardized opioidprescribing schedule (SOPS) after total hip arthroplasty (THA) and total knee arthroplasty (TKA) and evaluated opioid usage alongside Patient-Reported Outcomes Measurement Information System (PROMIS) pain interference scores. We hypothesized that opioid usage would be less than prescribed and reducing prescription would decrease consumption without negatively impacting the PROMIS scores. Methods: A prospective obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Pain and function are two relevant constructs for patients receiving knee arthroplasty. While there are a few studies on measurement properties of PROMIS short forms for pain and function in patients with knee osteoarthritis [ 7 9 ], nothing is known about the measurement properties in patients undergoing knee arthroplasty even though these tools are regarded as potentially useful for decision making [ 10 ] and have already been used for research in this patient group [ 11 , 12 ]. Two validation studies including osteoarthritis patients applied short forms of 6-item (pain interference) or 10-item (physical function) length [ 7 , 8 ], yet work examining the measurement properties of such or even shorter forms are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Pain and function are two relevant constructs for patients receiving knee arthroplasty. While there are a few studies on measurement properties of PROMIS short forms for pain and function in patients with knee osteoarthritis [ 7 9 ], nothing is known about the measurement properties in patients undergoing knee arthroplasty even though these tools are regarded as potentially useful for decision making [ 10 ] and have already been used for research in this patient group [ 11 , 12 ]. Two validation studies including osteoarthritis patients applied short forms of 6-item (pain interference) or 10-item (physical function) length [ 7 , 8 ], yet work examining the measurement properties of such or even shorter forms are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…25 In a 715-patient prospective study, Barnes and colleagues implemented a standardized opioid prescribing schedule (SOPS) of 60 oxycodone 5 mg tablets for TKR/THR, which resulted in a 27% and 31% reduction in cumulative opioid pills prescribed at discharge for TKR and THR, respectively. 26 Furthermore, they implemented SOPS of 30 oxycodone 5 mg tablets for THR surgeries based on outpatient opioid consumption trends resulting in a total 58% reduction compared with previous practice. In contrast to these studies, we observed a more significant reduction in cumulative MED (55% vs 34%) and quantity of pills prescribed (22% vs 8%) for TKR procedures compared with THR, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These results corroborate studies performed within the total hip and knee arthroplasty literature. 10 Although studies have demonstrated the impact of prescription-limiting legislation, including in knee and shoulder arthroscopy, previous literature has not evaluated PROMIS. 12 , 13 Previous literature has emphasized the importance of limiting postoperative opioid prescribing and the associated inferior patient outcomes following ACLR.…”
Section: Discussionmentioning
confidence: 99%
“… 9 The PROMIS 6B short form has been used in previous orthopaedic studies. 10 , 11 The PROMIS 6B short form is graded from 1 (not at all) to 5 (very much).…”
mentioning
confidence: 99%